In memory of Shah Abdul Hannan - Hasan, Md. Mahmudul (Media New Age Limited, 2021)
Shah Abdul Hannan was a great believer in Islam and lover of his country. He would reach out to any groups that work for one or both of these two entities. He had friends in major political parties and through them conveyed advice to the leadership for the betterment of Bangladesh. He always highlighted the good attributes of people and hardly spoke ill of others. I can write reams of paper to describe his honesty and magnanimity and his ability to love and forgive others. Suffice to say here that the country owes a profound debt of gratitude to Shah Abdul Hannan. I hope posterity will emulate his selflessness, nobility of character and intense patriotism. It is also my hope that his legacy will continue across future generations. I pray to God for his recompense in the life hereafter.